Weaponising Religion in Greece Post Economic Crisis: An Analysis of Far-Right Political Discourse from 2019 to 2024 - Samaras, Georgios (Journal of empirical theology, 2025)
This article analyses and compares how three far-right Greek parties - Greek Solution, Victory, and Voice of Reason - draw on religious narratives to advance exclusionary politics between 2019 and 2024. Applying Critical Discourse Analysis (CDA) to parliamentary debates, social media posts, public statements, and manifestos, the study illustrates how each party moulds Greek Orthodox Christianity into a strategic resource for shaping collective identity and promoting their agenda. Greek Solution blends conspiratorial rhetoric with sacred claims, presenting its leader as a guardian of Orthodoxy; Victory invokes doctrinaire authority through monastic endorsements, framing its positions as morally mandated; and Voice of Reason merges Orthodox references with global "anti-woke" themes to mobilise support. Together, these parties reinforce symbolic boundaries and solidify moral legitimacy for radical platforms, prompting significant implications for social cohesion, public trust, and democratic stability. The findings highlight the dynamic, context-specific power of religion within modern far-right populism.